Review of Data Mining with Weka Tool - Kaur, Kulwinder; Dhiman, Shivani (International Journal of Computer Sciences and Engineering, 2025)
Data mining is the process of extract unseen and hidden information from a large amount of data. It is a powerful technology that helps researchers to find the meaningful information by providing different tools and technologies. In this paper we focused on different tools, technologies and application area of data mining. Also discussed the weka tool,how we build data set for weka and how this data set is loaded on weka.